Patrimoine et mémoire de l’esclavage en Haïti : les vestiges de la société d’habitation coloniale - Jacques de Cauna (In Situ)
Haïti, first black republic in the world, is nowadays a true conservatory of the historical heritage of the eighteenth century slavery economics. The system was in fact based on the primary unit of the large-scale plantation, known in the French islands of America as habitation. Even in French, English or Spanish speaking Caribbean, it is there – on sugar estates, coffee, indigo or cotton plantations, or any other “places” – that lie the foundations of all creole societies, as well as the frame of everyday life, work and death, of the best part of the slaves – were they domestic or specialized workers, most of them creols (caribbean natives), or simple field workers, bossales (african born). The habitation system remained a long time after the end of slavery. Between 1975 and 1990, starting with localizations made through the help of eighteenth and nineteenth centuries archives followed by field inquiries in industrial archeology, more than 2 500 photos of remains of this kind of society in ancient Saint-Domingo have been taken in Haïti, along with its urban, military, religious or natural environment, in the purpose of keeping memory of an endangered heritage. Since 2009, thanks to the help of the CNRS, the CIRESC undertook to digitalize and put on line a selection of about 500 of these documents from the Jacques de Cauna fund. They are today presented for the first time. This tries to answer the wish of our Haïtian students at the very start of these operations : “Sugar estates are the sweat and blood of our ancestors. We have to show them respect”.